A negative photoresist composition, use thereof, and a method for forming a plated pattern

CN123010336APending Publication Date: 2026-10-30JIANGSU AISEN SEMICON MATERIAL CO LTD +3
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611288848.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明目的是:提供一种负性光刻胶组合物及其应用,以解决现有技术中厚膜光刻胶在电镀金工艺中分辨率不足的问题,进一步解决现有光刻胶在强碱性电镀金液中耐化学性不足以及单一分子量树脂对比度有限的问题

Benefits of technology

(1)通过采用重均分子量为15000和10000的两种丙烯酸树脂搭配,利用两种分子量树脂在碱性显影液中溶解速率的差异,提高了光刻胶的对比度和显影窗口,从而在35μm膜厚下实现了4μm的最小开口尺寸,而现有技术在同等膜厚下最小开口通常大于10μm。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123010336A_ABST
    Figure CN123010336A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of photoresist and particularly relates to a negative photoresist composition, application thereof and a method for forming an electroplating pattern. The composition comprises 20-40 parts by mass of acrylic resin, 1-5 parts by mass of a photo initiator combination, 10-30 parts by mass of a crosslinking agent, 50-80 parts by mass of a solvent and 0.05-0.1 parts by mass of an auxiliary agent; the acrylic resin comprises a first acrylic resin with a weight average molecular weight of 15000 and a second acrylic resin with a weight average molecular weight of 10000; the photo initiator combination comprises an oxime ester photo initiator and a free radical photo initiator, and the mass ratio of the oxime ester photo initiator to the free radical photo initiator is 1:2-1:4; and the acrylic resin is copolymerized from methyl methacrylate, isobornyl methacrylate, glycidyl acrylate, hydroxyethyl acrylate and isoprene. The composition is used in the electroplating gold process, can realize a high-resolution pattern with a 4-micron opening at a 35-micron film thickness, and has excellent resistance to strong-alkaline electroplating gold liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photoresist technology, specifically relating to a negative photoresist composition and its application, and a method for forming electroplated patterns. Background Technology

[0002] With the development of semiconductor packaging technology, electroplating gold is widely used in the manufacturing of semiconductor chip electrodes, LED gold contacts, and high-end packaging substrates. Photoresist, as a patterning mask, directly determines the precision and yield of the gold plating pattern through its resolution and electroplating resistance.

[0003] Patent document CN115793396B discloses a negative thick-film photoresist for advanced packaging. Its formulation includes 40-60 parts by weight of solvent, 30-50 parts by weight of acrylic resin, 3-10 parts by weight of initiator, 10-30 parts by weight of crosslinking agent, and 500-1500 ppm of additives. The photoresist has a viscosity of 3000-5000 mPa·s, and the acrylic resin has a molecular weight of 6000-15000. The acrylic resin is copolymerized from styrene, isoprene, methacrylic acid, isobornyl acrylate, and hydroxyethyl methacrylate. The initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP), and the crosslinking agent is a specific polyfunctional acrylate compound. This photoresist is used in advanced packaging copper pillar plating processes, achieving a film thickness of up to 110 μm, and producing steep copper pillar angles after plating.

[0004] However, the existing technology still has the following shortcomings: First, its resolution is limited, and it is difficult to achieve high-precision patterns with 4μm openings under a film thickness of 35μm, and the minimum opening size is usually greater than 10μm; Second, in the strong alkaline bath for gold electroplating (pH>9), the photoresist has insufficient chemical resistance and is prone to problems such as resin swelling, softening, and sidewall corrosion, resulting in defects such as seepage plating, drilling plating, and burr deformation at the edge of the pattern; Third, the photoresist uses acrylic resin with a single molecular weight, which has limited contrast, a narrow development window, and is prone to producing residual substrate film. Summary of the Invention

[0005] The purpose of this invention is to provide a negative photoresist composition and its application, in order to solve the problem of insufficient resolution of thick-film photoresists in the electroplating gold process in the prior art, and further solve the problems of insufficient chemical resistance of existing photoresists in strongly alkaline electroplating gold solutions and limited contrast of single molecular weight resins.

[0006] The technical solution of the present invention is as follows: In a first aspect, a negative photoresist composition is provided, comprising the following components in parts by weight: Acrylic resin: 20-40 parts; Photoinitiator combination: 1-5 parts; Crosslinking agent: 10-30 parts; Solvent: 50-80 parts; Additives: 0.05–0.1 parts; The acrylic resin comprises a first acrylic resin with a weight-average molecular weight of 15,000 and a second acrylic resin with a weight-average molecular weight of 10,000. The photoinitiator combination comprises oxime ester photoinitiators and free radical photoinitiators, and the mass ratio of oxime ester photoinitiators to free radical photoinitiators is 1:2 to 1:4.

[0007] Preferably, the mass ratio of the first acrylic resin to the second acrylic resin is 1:0.5 to 1:2.

[0008] Preferably, the acrylic resin comprises a polymer chain copolymerized from the following monomers: methacrylic acid, isobornyl methacrylate, glycidyl acrylate, hydroxyethyl acrylate, and isoprene.

[0009] Preferably, the oxime ester photoinitiator is selected from one or more of NCI-930, OEX-01, OEX-02, and WSP-960; the free radical photoinitiator is selected from one or more of BDK, BCIM, EMK, 907, and 1173.

[0010] Preferably, the crosslinking agent is selected from one or more of the polyfunctional acrylate crosslinking agents M9050, M309, M8100, M7100, and M408.

[0011] Preferably, the solvent is selected from one or more of propylene glycol methyl ether acetate, propylene glycol methyl ether, and cyclohexanone.

[0012] Preferably, the viscosity of the negative photoresist composition is 1500-2000 mPa·s.

[0013] Preferably, the additives include one or more of leveling agents, defoamers, and polymerization inhibitors.

[0014] Secondly, a method for forming an electroplated pattern is provided, comprising the following steps: (1) The negative photoresist composition of any one of claims 1 to 8 is coated on a substrate to form a photoresist layer; (2) The photoresist layer is heated, exposed and developed to form a photoresist pattern; (3) Electroplating is performed within the photoresist pattern to form an electroplated pattern; (4) Remove the photoresist pattern.

[0015] Thirdly, an application of a negative photoresist composition is provided, wherein the negative photoresist composition described in any of the above-mentioned embodiments is used as an electroplating mask in the electroplating gold process of semiconductor chips, LEDs or packaging substrates.

[0016] Compared with the prior art, the advantages of the present invention are: (1) By using two acrylic resins with weight average molecular weights of 15,000 and 10,000, the difference in dissolution rate of the two molecular weight resins in alkaline developer was utilized to improve the contrast and development window of the photoresist, thereby achieving a minimum opening size of 4 μm with a film thickness of 35 μm, while the minimum opening size of the existing technology is usually greater than 10 μm with the same film thickness.

[0017] (2) By using oxime ester photoinitiators and free radical photoinitiators in a synergistic combination and controlling the total amount of initiator in a low range of 1 to 5 parts, the absorption of ultraviolet light by the photoresist is reduced, allowing light energy to better penetrate the 35μm thick film, realizing vertical sidewall patterns with consistent width at the top and bottom, and avoiding the problem of pattern inverted cone or undercut caused by light attenuation.

[0018] (3) By using acrylic resin obtained by copolymerizing methacrylic acid, isobornyl methacrylate, glycidyl acrylate, hydroxyethyl acrylate and isoprene, combined with a multifunctional acrylate crosslinking agent, a dual crosslinking network containing free radical polymerization crosslinking and epoxy ring-opening crosslinking is formed. It has high crosslinking density and compactness. After electroplating in a strongly alkaline gold plating solution (pH>9, 50℃) for 60 minutes, the adhesive surface is intact without cracking or plating penetration. After electroplating, it is easy to completely peel off in N-methylpyrrolidone at 80℃ within 30 minutes. Attached Figure Description

[0019] The present invention will be further described below with reference to the accompanying drawings and embodiments: Figure 1 A scanning electron microscope image of the electroplated gold micropillar array obtained after coating, exposure, development, electroplating gold and removing the negative photoresist composition prepared in Example 1 of the present invention; Figure 2 The image shows a scanning electron microscope image of an electroplated gold micropillar array obtained under the same conditions using the negative photoresist composition prepared in Comparative Example 1 of the present invention. Figure 3 A scanning electron microscope image of the unplated photoresist pattern after development of the negative photoresist composition prepared in Example 1 of the present invention; Figure 4 A scanning electron microscope image of the unplated photoresist pattern after development of the negative photoresist composition prepared in Comparative Example 2 of the present invention; Figure 5This is a magnified scanning electron microscope image of the electroplated gold micropillar array obtained after coating, exposure, development, electroplating, and resist removal in Embodiment 1 of the present invention. Detailed Implementation

[0020] The present invention will be further described in detail below with reference to specific embodiments: I. Synthesis of Acrylic Resin First, three acrylic resins were synthesized as the base raw materials for subsequent negative photoresist compositions.

[0021] 1. Synthesis of a first acrylic resin (resin A) with a weight-average molecular weight of 15,000 In a 1000 mL four-necked flask equipped with a mechanical stirrer, thermometer, reflux condenser, and nitrogen inlet, add 15 g of methacrylic acid, 30 g of isobornyl methacrylate, 25 g of glycidyl acrylate, 20 g of hydroxyethyl acrylate, 10 g of isoprene, 200 g of propylene glycol methyl ether acetate, and 2 g of azobisisobutyronitrile (AIBN). Purge with high-purity nitrogen for 30 minutes, raise the temperature to 80 °C, and stir the reaction under nitrogen protection for 6 hours. After the reaction is complete, slowly pour the reaction solution into 2000 mL of methanol, stirring to precipitate the polymer. Filter the precipitate, wash it three times with methanol (100 mL each time), and dry the filter cake in a vacuum drying oven at 50 °C to constant weight (approximately 24 hours) to obtain a white solid acrylic resin. The weight-average molecular weight (Mw) was determined to be 15,000 and the molecular weight distribution (Mw / Mn) was 2.3 by gel permeation chromatography (GPC) with tetrahydrofuran as the mobile phase and polystyrene as the standard. The acid value was determined to be 85 mg KOH / g by potassium hydroxide-ethanol titration.

[0022] 2. Synthesis of a second acrylic resin (resin B) with a weight-average molecular weight of 10,000 In a 1000 mL four-necked flask equipped with a mechanical stirrer, thermometer, reflux condenser, and nitrogen inlet, 15 g of methacrylic acid, 30 g of isobornyl methacrylate, 25 g of glycidyl acrylate, 20 g of hydroxyethyl acrylate, 10 g of isoprene, 200 g of propylene glycol methyl ether acetate, and 3 g of azobisisobutyronitrile (AIBN) were added. Nitrogen gas was bubbled through the flask for 30 minutes, the temperature was raised to 80 °C, and the mixture was stirred for 4 hours. After the reaction was complete, the reaction solution was poured into 2000 mL of methanol to precipitate the resin. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 50 °C to constant weight, yielding a white solid acrylic resin. GPC analysis showed that the resin had a weight-average molecular weight of 10,000, a molecular weight distribution of 2.2, and an acid value of 86 mg KOH / g.

[0023] It should be noted that the first acrylic resin (resin A) and the second acrylic resin (resin B) of this invention use the exact same monomer composition (methacrylic acid, isobornyl methacrylate, glycidyl acrylate, hydroxyethyl acrylate, and isoprene), and the molecular weight is controlled only by adjusting the amount of polymerization initiator (AIBN). Specifically, 2g of AIBN yields resin A with a molecular weight of 15,000, and 3g of AIBN yields resin B with a molecular weight of 10,000. This invention uses a combination of resins with "the same composition but different molecular weights," rather than altering the chemical structure of the resins.

[0024] 3. Comparison with synthesis using a single molecular weight acrylic resin (resin C) Following the method of Preparation Example 1, but adjusting the amount of AIBN to 2.5g, the reaction time to 5 hours, and keeping other conditions unchanged, an acrylic resin with a weight-average molecular weight of 12000, a molecular weight distribution of 2.4, and an acid value of 85mgKOH / g was obtained.

[0025] II. Formulation and Performance Testing of Negative Photoresist Compositions The following details the composition preparation methods, coating processes, photolithography processes, electroplating processes, and corresponding performance test results for each embodiment and comparative example. To ensure comparability of results, all embodiments and comparative examples used the same testing equipment and conditions.

[0026] Coating, photolithography, electroplating, and general resist removal process (unless otherwise specified): The photoresist composition is coated onto a 6-inch silicon wafer using spin coating. The spin coating parameters are: spin speed 1200 rpm, acceleration 500 rpm / s, and time 90 s. The wafer is then placed in an oven at 120°C for 5 minutes to remove the solvent. Contact exposure is performed using a UV exposure machine (ultra-high pressure mercury lamp, i-line 365nm as the main peak) at an exposure dose of 1200 mJ / cm². 2 After exposure, the sample was post-baked (PEB) for 10 minutes in a 120°C oven. Static development was then performed for 2 minutes at 23°C using a 2.38wt% tetramethylammonium hydroxide (TMAH) aqueous solution, followed by rinsing with deionized water for 1 minute and drying with nitrogen. The gold plating bath formula was: potassium gold cyanide 8 g / L, dipotassium hydrogen phosphate 30 g / L, citric acid 15 g / L, pH adjusted to 9.5 with potassium hydroxide, and temperature 50°C. Electroplating conditions: current density 1 A / dm³. 2 The process takes 60 minutes. After electroplating, rinse with deionized water, then immerse in N-methylpyrrolidone (NMP) at 80°C for 30 minutes to remove the adhesive, then rinse with deionized water and dry with nitrogen.

[0027] Test methods: Film thickness and uniformity were measured using a film thickness meter; the pattern after development and the gold pattern after electroplating were observed using a scanning electron microscope, and the minimum opening size and sidewall angle were measured; the viscosity was measured using a rotational viscometer (25℃, 50rpm); the surface cracking and plating were observed under SEM after electroplating; the residue was observed under an optical microscope (200x) after adhesive removal.

[0028] Example 1

[0029] Weigh out 12 parts by weight of resin A (Mw15000), 12 parts by weight of resin B (Mw10000), 1 part by weight of oxime ester photoinitiator NCI-9301, 3 parts by weight of free radical photoinitiator 9073, 15 parts by weight of crosslinking agent M90501, 60 parts by weight of propylene glycol methyl ether acetate (PGMEA), 0.06 parts by weight (600ppm) of leveling agent BYK-333, and 0.05 parts by weight (500ppm) of defoamer BYK-065. Add all the above components to a 250mL glass beaker and stir at 1000rpm for 2 hours with a high-speed dispersing stirrer until completely dissolved, obtaining a clear and transparent yellow solution. After filtration through a 5μm polytetrafluoroethylene filter membrane, the viscosity was measured to be 1680mPa·s.

[0030] The photoresist is coated, exposed, and developed according to standard procedures. After development, the photoresist pattern is observed under a scanning electron microscope. Figure 3 As shown, the photoresist formed an array of micropillars with a height of approximately 35 μm and a diameter of approximately 2.98 μm, with an aspect ratio of approximately 11.7:1. The sidewalls of the micropillars are smooth and vertical, with no obvious tilting or undercutting observed. The minimum opening size is 4 μm, and the sidewalls are steep, with no obvious tilting or undercutting observed. This high resolution is due to two factors: firstly, the combination of 15,000 and 10,000 molecular weight resins, whose different solubility rates in the developer increase the solubility contrast between the exposed and unexposed areas; secondly, the low amount of the oxime ester photoinitiator NCI-930 (only 4 parts of total initiator), which reduces the absorption of 365 nm ultraviolet light by the photoresist, allowing light energy to effectively penetrate the 35 μm thick film and ensuring sufficient cross-linking at the bottom of the film. From an optical perspective, the absorption of ultraviolet light by photoresist films follows the Lambert-Beer law: A = ε·c·L, where A is the absorbance, ε is the molar absorptivity of the initiator at 365 nm, c is the initiator concentration, and L is the optical path length (film thickness). When the total initiator content is reduced from the conventional 8-12 parts (approximately 0.8%-1.2% by mass) to the 1-5 parts (approximately 0.1%-0.5% by mass) of this invention, the initiator concentration c decreases by approximately 60%-80%, resulting in a proportional decrease in absorbance A. According to the light intensity attenuation formula I = I0·10 (-A)The light intensity at the bottom of the 35μm film thickness is significantly improved. Taking Example 1 as an example, the total initiator dosage is 4 parts (about 0.4%), the absorbance is about 1 / 3 of the conventional dosage (12 parts, about 1.2%), and the light intensity at the bottom is about 5 times that of the conventional dosage, thereby ensuring full cross-linking at the bottom of the film layer and achieving a vertical sidewall pattern with consistent width at the top and bottom.

[0031] Subsequently, gold plating was performed. After 60 minutes of electroplating, the substrate was removed and observed under SEM. Figure 1 As shown, the electroplated gold micropillars are approximately 33.9 μm high and 3.53 μm in diameter. The micropillars grow vertically, have smooth, burr-free sidewalls, and show no bridging or residue between them. This indicates that the photoresist mask remained intact in the strongly alkaline gold plating solution, without cracking or plating penetration. Figure 5 As shown, under local high-magnification magnification, it can be clearly seen that the sidewalls of the micropillars are extremely smooth and flat, without obvious etching ripples or rough particles; the top edge of the micropillars is rounded, without burrs or residues, further confirming that the photoresist composition of the present invention has excellent anti-permeability and film uniformity during development and electroplating, and can effectively avoid the generation of sidewall defects. This is because the acrylic resin in this embodiment contains glycidyl acrylate, whose epoxy groups undergo ring-opening crosslinking with carboxyl and hydroxyl groups during the post-baking process, forming a dual crosslinking network of free radical polymerization and epoxy ring opening, with high crosslinking density and strong chemical resistance. To verify the occurrence of epoxy ring-opening reaction, Fourier transform infrared spectroscopy (FTIR) analysis was performed on the photoresist film of Example 1. The photoresist was coated on a silicon wafer, and infrared spectra were collected after exposure (without post-baking) and after post-baking (120°C, 10 min). The results show that after post-baking, the film is located at 910 cm⁻¹. -1 The characteristic absorption peak of the nearby epoxy group is significantly weakened (peak area reduced), and it is located at 3400 cm⁻¹. -1 The absorption peak of the nearby hydroxyl groups is enhanced. This indicates that during the post-baking process, the epoxy groups provided by glycidyl acrylate undergo ring-opening addition reactions with the carboxyl groups provided by methacrylic acid and the hydroxyl groups provided by hydroxyethyl acrylate, forming ester bonds and new hydroxyl groups. Therefore, the photoresist of the present invention forms a dual crosslinking network of free radical polymerization crosslinking (exposure stage) and epoxy ring-opening crosslinking (post-baking stage), with a significantly higher crosslinking density than systems relying solely on free radical polymerization crosslinking. This is the fundamental reason for its resistance to strongly alkaline gold plating solutions.

[0032] Finally, the photoresist was removed using standard procedures. After removal, the substrate surface was observed under an optical microscope to be completely clean, with no photoresist residue. The reason for the complete removal is that although the double cross-linked network is dense, it is not over-crosslinked. NMP can effectively swell and dissolve the cross-linked network at 80°C, and the ester bonds in the acrylic resin can partially break at high temperatures, promoting peeling.

[0033] Example 2

[0034] Weigh out 10 parts by weight of resin A (Mw15000), 15 parts by weight of resin B (Mw10000), 0.8 parts by weight of oxime ester photoinitiator OEX-01, 2.2 parts by weight of free radical photoinitiator BDK, 20 parts by weight of crosslinking agent M309, 55 parts by weight of propylene glycol methyl ether (PGME), 0.07 parts by weight (700 ppm) of leveling agent BYK-349, and 0.03 parts by weight (300 ppm) of polymerization inhibitor p-methoxyphenol. The preparation method is the same as in Example 1, and the viscosity was measured to be 1820 mPa·s.

[0035] The coating, exposure, development, gold plating, and resist removal processes were performed according to standard procedures. After development, the minimum opening size was 5μm, and the sidewalls were steep. After electroplating, the resist surface was intact without cracks or plating seepage, and no residue remained after resist removal.

[0036] Example 3

[0037] Weigh out 15 parts by weight of resin A (Mw15000), 10 parts by weight of resin B (Mw10000), 0.6 parts by weight of oxime ester photoinitiator WSP-960, 2.4 parts by weight of free radical photoinitiator 1173, 12 parts by weight of crosslinking agent M8100, 65 parts by weight of cyclohexanone, and 0.05 parts by weight (500 ppm) of defoamer Airex900. The preparation method is the same as in Example 1, and the viscosity was measured to be 1550 mPa·s.

[0038] Tested according to standard procedures, the minimum opening size after development is 4μm, with steep sidewalls. After electroplating, the adhesive surface is intact without cracks or plating seepage, and there is no residue after adhesive removal.

[0039] Example 4

[0040] Weigh out 13 parts by weight of resin A (Mw15000), 13 parts by weight of resin B (Mw10000), 0.5 parts by weight of oxime ester photoinitiator OEX-02, 1.5 parts by weight of free radical photoinitiator EMK, 25 parts by weight of crosslinking agent M7100, 70 parts by weight of mixed solvent (PGMEA:PGME=1:1), 0.08 parts by weight (800ppm) of leveling agent BYK-333, and 0.04 parts by weight (400ppm) of defoamer BYK-065. The preparation method is the same as in Example 1, and the viscosity was measured to be 1900 mPa·s.

[0041] Tested according to standard procedures, the minimum opening size after development is 5μm, and the sidewalls are steep. After electroplating, the adhesive surface is intact without cracks or plating seepage, and there is no residue after adhesive removal.

[0042] Example 5

[0043] Weigh out 14 parts by weight of resin A (Mw15000), 14 parts by weight of resin B (Mw10000), 0.7 parts by weight of oxime ester photoinitiator NCI-930, 2.1 parts by weight of free radical photoinitiator BCIM, 18 parts by weight of crosslinking agent M408, 62 parts by weight of PGMEA, 0.05 parts by weight (500ppm) of leveling agent BYK-333, 0.05 parts by weight (500ppm) of defoamer BYK-065, and 0.02 parts by weight (200ppm) of polymerization inhibitor hydroquinone. The preparation method is the same as in Example 1, and the viscosity was measured to be 1750 mPa·s.

[0044] Tested according to standard procedures, the minimum opening size after development is 4μm, with steep sidewalls. After electroplating, the adhesive surface is intact without cracks or plating seepage, and there is no residue after adhesive removal.

[0045] Comparative Example 1 Weigh 24 parts by weight of resin C (Mw12000), with the remaining components being exactly the same as in Example 1: 1 part of oxime ester photoinitiator NCI-930, 3 parts of free radical photoinitiator 907, 15 parts of crosslinking agent M9050, 60 parts of PGMEA, 0.06 parts of BYK-333, and 0.05 parts of BYK-065. The preparation method was the same as in Example 1, and the viscosity was measured to be 1650 mPa·s.

[0046] The test was conducted according to a standard process. After development, the minimum opening size was only 10 μm, the sidewalls were noticeably tilted, and the resolution was significantly lower than in Example 1. This is because the solubility contrast of a single molecular weight resin is relatively small, resulting in a narrow development window. After gold plating, observation under SEM showed... Figure 2 As shown, the electroplated gold micropillars are approximately 33.6 μm high and 3.09 μm in diameter. Some micropillars have burrs and irregular protrusions on their sidewalls, and a few show lateral spread due to plating seepage at the bottom. A small amount of metal residue remains between the pillars. This is because resin C does not contain glycidyl acrylate, thus failing to form a double cross-linked network, resulting in insufficient cross-linking density and poor alkali resistance. Slight residue remains after removing the adhesive (approximately 2% of the area).

[0047] Comparative Example 2 Weigh out 12 parts of resin A, 12 parts of resin B, 4 parts of oxime ester photoinitiator NCI-930, and 9078 parts of free radical photoinitiator (total initiator 12 parts). The remaining components are the same as in Example 1. The preparation method is the same as in Example 1, and the viscosity was measured to be 1720 mPa·s.

[0048] Testing was performed according to standard procedures. After development, the photoresist pattern was observed under SEM. For example... Figure 4As shown, the height of the micropillars is approximately 35.0 μm, and the measured diameter fluctuates between 3.1 and 3.8 μm (with one measurement of approximately 3.36 μm). Some micropillars exhibit significant undercutting (concave sidewalls), severe rounding at the top, uneven spacing, and photoresist residue in some areas. The smallest opening is only 8 μm, and the sidewalls show obvious tilting and undercutting. This is because the initiator dosage was too high (12 parts), which enhanced the absorption of ultraviolet light by the photoresist, leading to excessive cross-linking at the top and insufficient cross-linking at the bottom due to insufficient light intensity, resulting in undercutting during development. Slight plating penetration occurred after electroplating, and slight residue remained after photoresist removal (approximately 1% of the area).

[0049] Comparative Example 3 Weigh out 12 parts of resin A, 12 parts of resin B, and 9074 parts of free radical photoinitiator (excluding oxime ester photoinitiators). The remaining components are the same as in Example 1. The preparation method is the same as in Example 1, and the viscosity was measured to be 1600 mPa·s.

[0050] Testing was conducted according to standard procedures. After development, the smallest opening was only 12μm, with severe sidewall tilting and the worst resolution. Significant plating seepage occurred after electroplating, leaving approximately 5% of the area remaining after resist removal. This is due to the lack of oxime ester photoinitiators, resulting in insufficient photosensitivity and incomplete cross-linking.

[0051] Comparative Example 4 This comparative example aims to verify whether the resolution level of this invention can be achieved by changing only the initiator system without changing the resin composition.

[0052] Resin D was prepared according to the acrylic resin formulation disclosed in patent document CN115793396B: 10 parts styrene, 6.9 parts isoprene, 9 parts methacrylic acid, 21 parts isobornyl acrylate, 13 parts hydroxyethyl methacrylate, 75 parts xylene, and 0.8 parts tert-butyl perbenzoate, and reacted at 70°C for 3 hours. The weight-average molecular weight of this resin is 10,000, and it does not contain glycidyl acrylate.

[0053] Weigh out 24 parts by weight of resin D (replacing resin A + resin B in Example 1), 1 part of oxime ester photoinitiator NCI-930, 3 parts of free radical photoinitiator 907, 15 parts of crosslinking agent M9050, 60 parts of PGMEA, 0.06 parts of BYK-333, and 0.05 parts of BYK-065. The preparation method is the same as in Example 1, and the viscosity was measured to be 1580 mPa·s.

[0054] Tests were conducted according to standard procedures. After development, the minimum opening size was 9 μm, with a noticeable tilting of the sidewalls. Significant plating seepage occurred after electroplating, leaving approximately 3% of the area remaining after resist removal. These results indicate that even with the low-dosage oxime ester initiator system of this invention, without the specific resin composition of this invention (especially the absence of glycidyl acrylate), a double cross-linked network cannot be formed, resulting in insufficient alkali resistance. Furthermore, the single molecular weight resin (without a combination of different molecular weights) leads to insufficient contrast, preventing a resolution of 4 μm.

[0055] III. Summary of Performance Test Results The key performance parameters of all the above embodiments and comparative examples are summarized in Table 1 below.

[0056] Table 1: Comprehensive performance test results of each group of negative photoresist compositions

[0057] As can be seen from the data in Table 1, Examples 1 to 5 of the present invention all achieved a minimum aperture resolution of 4 to 5 μm with a film thickness of 35 μm, a sidewall angle of 86 to 89°, no cracking or plating after electroplating, and complete removal of adhesive; while Comparative Example 1, which uses a single molecular weight resin, had a resolution of only 10 μm, and cracking and plating occurred after electroplating; Example 2, which used an excessive amount of initiator, had a resolution of 8 μm, a sidewall angle of 80°, and undercutting and plating occurred; while Comparative Example 3, which did not use an oxime ester photoinitiator, had a resolution of 12 μm and severe plating.

[0058] Comparative Example 4 used a prior art resin formulation (free of glycidyl acrylate, single molecular weight) combined with the low-dosage oxime ester initiator system of this invention. Its minimum opening was 9 μm, and its sidewall angle was 81°. Significant plating penetration occurred after electroplating, and slight residue remained after resist removal (approximately 3% of the area). Compared to Examples 1-5, Comparative Example 4 showed shortcomings in both resolution and electroplating resistance.

[0059] Therefore, it can be seen that the present invention significantly improves the resolution and resistance to strong alkaline electroplating solutions of photoresist by combining resins of different molecular weights, using low amounts of oxime ester initiators, and forming a dual crosslinking network with specific acrylic resins and crosslinking agents.

[0060] The above embodiments are merely illustrative of the technical concept and features of the present invention, intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and should not be construed as limiting the scope of protection of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects. The scope of the present invention is defined by the appended claims rather than the foregoing description, and thus all changes falling within the meaning and scope of the equivalents of the claims are intended to be included within the present invention.

Claims

1. A negative photoresist composition, characterized in that, The components comprise the following parts by weight: Acrylic resin: 20-40 parts; Photoinitiator combination: 1-5 parts; Crosslinking agent: 10-30 parts; Solvent: 50-80 parts; Additives: 0.05–0.1 parts; The acrylic resin comprises a first acrylic resin with a weight-average molecular weight of 15,000 and a second acrylic resin with a weight-average molecular weight of 10,000. The photoinitiator combination comprises oxime ester photoinitiators and free radical photoinitiators, and the mass ratio of oxime ester photoinitiators to free radical photoinitiators is 1:2 to 1:

4.

2. The negative photoresist composition according to claim 1, characterized in that, The mass ratio of the first acrylic resin to the second acrylic resin is 1:0.5 to 1:

2.

3. The negative photoresist composition according to claim 1, characterized in that, The acrylic resin comprises a polymer chain copolymerized from the following monomers: methacrylic acid, isobornyl methacrylate, glycidyl acrylate, hydroxyethyl acrylate, and isoprene.

4. The negative photoresist composition according to claim 1, characterized in that, The oxime ester photoinitiator is selected from one or more of NCI-930, OEX-01, OEX-02, and WSP-960; the free radical photoinitiator is selected from one or more of BDK, BCIM, EMK, 907, and 1173.

5. The negative photoresist composition according to claim 1, characterized in that, The crosslinking agent is selected from one or more of the polyfunctional acrylate crosslinking agents M9050, M309, M8100, M7100, and M408.

6. The negative photoresist composition according to claim 1, characterized in that, The solvent is selected from one or more of propylene glycol methyl ether acetate, propylene glycol methyl ether, and cyclohexanone.

7. The negative photoresist composition according to claim 1, characterized in that, The viscosity of the negative photoresist composition is 1500–2000 mPa·s.

8. The negative photoresist composition according to claim 1, characterized in that, The additives include one or more of leveling agents, defoamers, and polymerization inhibitors.

9. A method for forming an electroplated pattern, characterized in that, Includes the following steps: (1) The negative photoresist composition of any one of claims 1 to 8 is coated on a substrate to form a photoresist layer; (2) The photoresist layer is heated, exposed and developed to form a photoresist pattern; (3) Electroplating is performed within the photoresist pattern to form an electroplated pattern; (4) Remove the photoresist pattern.

10. The application of the negative photoresist composition according to any one of claims 1 to 8 as an electroplating mask in the electroplating gold process of semiconductor chips, LEDs or packaging substrates.

Citation Information

Patent Citations

  • A negative thick film photoresist for advanced packaging

    CN115793396B